Treatment satisfaction and improvement in health‐related quality of life with onabotulinumtoxinA in patients with urinary incontinence due to neurogenic detrusor overactivity123. Issue 3 (10th September 2012) - Sussman, David; Patel, Vaishali; Del Popolo, Giulio; Lam, Wayne; Globe, Denise; Pommerville, Peter
Abstract Aims OnabotulinumtoxinA significantly reduces urinary incontinence (UI) and improves bladder management in patients with neurogenic detrusor overactivity (NDO). We evaluated the impact of onabotulinumtoxinA on patient‐reported outcomes (PROs) in patients with UI due to NDO in a double‐blind, placebo‐controlled study. Methods Patients with UI due to NDO (from multiple sclerosis or spinal cord injury) were randomized to intradetrusor placebo (n = 92) or onabotulinumtoxinA 200 U (n = 92) or 300 U (n = 91). PROs included Incontinence Quality of Life (I‐QOL) Questionnaire to assess health‐related quality of life (HRQoL), the 16‐item modified Overactive Bladder‐Patient Satisfaction with Treatment Questionnaire (OAB‐PSTQ) to assess treatment satisfaction, and Patient Global Assessment to assess treatment goal achievement. Results Mean improvement in I‐QOL total score at weeks 6 and 12 was significantly greater with both onabotulinumtoxinA 200 U and 300 U versus placebo (Δ12.3 for 200 U and Δ14.9 for 300 U vs. placebo; P < 0.001), and was clinically meaningful. For those patients who completed the OAB‐PSTQ, improvement in satisfaction at weeks 6 and 12 was significantly greater for onabotulinumtoxinA versus placebo (P < 0.001, all comparisons). At 6 weeks, greater proportions of onabotulinumtoxinA‐treated patients than placebo reported being somewhat or very satisfied (200 U, 77.5% and 300 U, 67.8% vs. placebo, 39.5%), and significant progress toward or complete achievement of primary treatment goal (200 U, 62.9% and 300 U, 61.6% vs. placebo, 16.5%). Conclusions NDO patients treated with onabotulinumtoxinA 200 or 300 U had significantly greater improvement in HRQoL and greater treatment satisfaction compared with placebo‐treated patients, with no clinically relevant differences between onabotulinumtoxinA doses. Neurourol. Urodynam. 32: 242–249, 2013. © 2012 Wiley Periodicals, Inc.